2021
DOI: 10.3390/v13101899
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies to S and N SARS-CoV-2 Proteins as Probes to Assess Structural and Antigenic Properties of Coronaviruses

Abstract: Antibodies targeting the spike (S) and nucleocapsid (N) proteins of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are essential tools. In addition to important roles in the treatment and diagnosis of infection, the availability of high-quality specific antibodies for the S and N proteins is essential to facilitate basic research of virus replication and in the characterization of mutations responsible for variants of concern. We have developed panels of mouse and rabbit monoclonal antibodies (mA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In our study, a high affinity and specificity on detection of S1 protein was achieved in the presence of CAb immobilization onto the electrode surface by using rabbit monoclonal antibody similarly to the results of earlier studies confirming the higher affinity and specificity of rabbit monoclonal antibodies [ 23 , 24 ]. By the immobilization of rabbit monoclonal antibody onto the electrode surface, the stability of immuno-complex between Cab and its target antigen occurred on the electrode surface is ensured.…”
Section: Resultssupporting
confidence: 87%
“…In our study, a high affinity and specificity on detection of S1 protein was achieved in the presence of CAb immobilization onto the electrode surface by using rabbit monoclonal antibody similarly to the results of earlier studies confirming the higher affinity and specificity of rabbit monoclonal antibodies [ 23 , 24 ]. By the immobilization of rabbit monoclonal antibody onto the electrode surface, the stability of immuno-complex between Cab and its target antigen occurred on the electrode surface is ensured.…”
Section: Resultssupporting
confidence: 87%
“…Monoclonal antibodies are generated from B-cells isolated from the immunized animals that are subsequently immortalized and selected for their abilities to produce single high-affinity antibodies towards well-defined epitopes. A number of monoclonal antibodies have been developed that specifically bind SARS-CoV-2 antigens [39][40][41][42]. Monoclonal antibodies, which can be generated in large qualified batches via contract research organizations, are commonly used in clinical diagnostic assays including enzyme-linked immunosorbent assays (ELISA), plaque reduction neutralization assays (PRNT), and lateral flow assays (LFA).…”
Section: Antibody-based Biosensorsmentioning
confidence: 99%
“…In addition, many immunological studies have shown that N protein interacts with host proteins to induce immune responses or regulate the cell cycle of host cells after viral infection [15] , [16] , [17] , [18] . Many antibodies to the N protein can be detected in patients with COVID-19 to be used as a basis for diagnosis and treatment [19] , [20] . The nucleocapsid protein of coronavirus contains two main domains: the N-terminal domain (NTD) and the C-terminal domain (CTD) [21] .…”
Section: Introductionmentioning
confidence: 99%